The First Complete Chloroplast Genome Sequence of Secale strictum subsp. africanum Stapf (Poaceae), the Putative Ancestor of the Genus Secale - Lidia Skuza; Piotr Androsiuk; Romain Gastineau; Magdalena Achrem; Łukasz Paukszto; Jan Paweł Jastrzębski (Current Issues in Molecular Biology)
Secale strictum ssp. africanum (synonym Secale africanum), a putative ancestor of the genus Secale, has been classified within Secale strictum, although recent phylogenetic studies suggest that it represents a distinct species. This study reports the first complete chloroplast genome of S. africanum, highlighting its structure, genetic composition, and phylogenetic relationships within Secale and related Triticiceae species. Phylogeny reconstruction based on the maximum-likelihood method reveals notable genetic similarity between S. strictum and S. africanum, supporting their genetic and phylogenetic distinction. Here, we assembled the complete, annotated chloroplast genome sequence of Secale strictum ssp. africanum. The genome is 137,068 base pair (bp) long. It is the first complete chloroplast genome that can be used as a reference genome for further analysis. The genome can be accessed on GenBank with the accession number OQ700974. This work sheds light on the evolutionary history of Secale and contributes to our understanding of chloroplast genomics in cereal ancestors, with potential applications in improving cereal crop resilience, advancing breeding strategies, and informing conservation efforts for genetic diversity.